DESIGN OF ZERO RUNOFF SYSTEM AT IPB DARMAGA CAMPUS, BOGOR, WEST JAVA - Ihsan, Muhammad; Setiawan, Budi Indra; Pandjaitan, Nora H (Jurnal Teknik Sipil dan Lingkungan, 2016)
Bogor Agricultural University (IPB) Campus is an urban area that experienced flooding when heavy rain occurred, especially at Graha Widya Wisuda (GWW)’s parking lot, Kamper Street (FEMA), Meranti Street, and Tanjung Street. The drainage system of IPB campus is a conventional system. It drain surface runoff as fast as possible to the outlet. Zero Runoff System (ZROS) is one of technologies to minimize runoff using water storage. The advantages of ZROS are runoff minimization, local aquifer’s recharge, and damage mitigation on public facilities. This research aimed to design ZROS at IPB Campus that capable to minimize surface runoff. This research started by water catchment area (WCA) delineation, design rainfall and peak runoff analysis, infiltration rate measurement, and ZROS design calculation. Based on frequency analysis the design rainfall was 125.68 mm. Sub-sub-WCA 1-1C (3 locations), 1-1B, 2-1B, and 2-2A were the flooding’s location. Water pocket is the proposed technology to be applied in ZROS. To mitigate flooding, sub-sub-WCA 1-1B, 1-1C, 2-1B, and 2-2A needed 44 units of water pockets with length of 1.20 m (sub-sub-DTA 1-1B, 2-1B, dan 2-2A) and 1.60 m (sub-sub-DTA 1-1C),  with depth ranged from 2.41 m to 3.40 m. Keywords: drainage, flood, runoff, water balance, ZROS